Stereo capture unit for real-time computer vision, featuring hardware-accelerated digital filter design - Kramberger, Iztok (Informacije MIDEM, 2003)
Real-time processing plays an important role in the achievement of more natural and physically intuitive ways for user-machine interaction. The main scope of this article is the development of a computer vision stereo capture unit that would fulfill more natural user-machine interaction within contemporary mobi le telecommunication solutions. One of the main problems with current mobi le devices is the restricted size of the showing area and the data input methods as a manner of device navigation. One of the most convenient ways to solve this problem is the use of gesture recognition with invirtual or augmented reality applications. In such cases the skin color can be a very comprehensive feature and so color tracking has been used to achieve the required goal. We have developed a method of color and spatial filtering for the purpose of indicating skin features and constituting skin formations within the level of the binary mask stream. A new stereo capture unit hardware structure with an accelerated digital nonlinear parametrical filter is shown. This features real-time searching for skin colored regions ina two-dimensional image stream where the parametrical design of the color filter al so offers color detection in a comprehensive way. This parametrical scheme for the color filter enables automatic simultaneous adaptation of parameters due to changes in scene luminance and automatic adaptation possibilities of the color filter to the different types of skin.
Keywords: digitalni filtri; digitalno procesiranje; filtriranje; koža; obdelava slik; računalniški vid